Expression patterns and prognostic role of m6A RNA methylation regulators in Non-small Cell Lung Cancer: M6A RNA methylation in Non-Small Cell Lung Cancer - Zhang, Ming; Yang, Congbo; Dong, Wen; Zhao, Yutao; Chen, Nan; Gao, Change (Cellular and Molecular Biology, 2024)
To investigate the expression pattern and prognostic role of m6A RNA methylation regulators in non-small cell lung cancer (NSCLC), we downloaded data from 422 patients from The Cancer Genome Atlas (TCGA) database. The relationship between the expression levels of m6A RNA methylation regulators and clinicopathological variables of NSCLC was analysed using R language. By analysing glioma data in TCGA, we found that a prognostic risk score model could be constructed based on 18 genes with m6A methylation modification. m6A gene alterations were significantly associated with tumour grade and tumour stage. Least Absolute Shrinkage and Selection Operator (LASSO) Cox regression models were used to identify 2 m6A RNA methylation modifiers: IFG2BP2, and METTL14 to construct risk profiles. Based on the risk profile, patients were divided into high-risk and low-risk groups. The overall survival rate of the low-risk group was significantly higher than that of the high-risk group. The results suggest that the prognostic risk score model constructed by m6A methylation regulators can predict the prognosis of glioma patients. IFG2BP2 and METTL14 may be the key m6A methylation regulators involved in the development of NSCLC and can be used as the molecular markers for the prognosis of NSCLC.